A Rare Case of Anaphylaxis to Methimazole in a Patient With Graves’ Disease - Garg, Dave (J Endocr Soc, 2021)
We present the case of a patient with Graves’ Disease (GD) who developed anaphylaxis to methimazole (MMI) necessitating hospitalization, emergent treatment and ultimately urgent total thyroidectomy. While the most common adverse reactions to thionamides include hepatotoxicity, agranulocytosis, pruritis, and urticaria, delayed anaphylaxis has been reported. A 25-year-old woman was diagnosed with GD two years prior to presentation during an admission for syncope. She was started on MMI 10 mg twice a day and propranolol 10 mg three times a day, which she took for roughly one year until she ran out of medication and was lost to follow-up. She remained off MMI until she re-presented several months later grossly thyrotoxic, complaining of fatigue, heat intolerance, unintentional weight loss, blurry vision, and palpitations. Labs were significant for TSH <0.02 mIU/L (normal 0.3-4.7), free T4 >7 ng/dL (normal 0.8-1.7), free T3 >2900 pg/dL (normal 222-383), and thyroid stimulating immunoglobulin (TSI) >500 (normal ≤122). She was restarted on propranolol and MMI 10 mg twice a day which was quickly increased to 20 mg twice a day. Two weeks after restarting MMI, the patient presented to the ER with a diffuse pruritic rash and was treated with antihistamines and steroids. She clinically improved and was discharged in stable condition. Two days later, her symptoms recurred along with flushing, facial/lip swelling, and dysphagia. She presented to our hospital with evidence of angioedema and difficulty breathing. Based on her presentation, anaphylaxis was diagnosed, and she was given intramuscular epinephrine. She was also started on glucocorticoids, H1/H2 blockers and montelukast and was admitted to the ICU for close monitoring. Over the next few days, her symptoms improved. As there was no other recent novel exposure, her anaphylactic reaction was attributed to MMI. Given the life-threatening nature of the reaction, there was concern for trialing propylthiouracil (PTU) due to its known cross-reactivity with MMI. Thus, treatment with propranolol, steroids and potassium iodide was initiated with improvement in her thyroid labs. As the patient would be unable to tolerate anti-thyroid agents in the future, it was decided to pursue definitive treatment with total thyroidectomy given the presence of eye disease. Anaphylaxis secondary to MMI is very rare, and less than a handful of cases have been reported. However, they seem to share two key features: their occurrence with higher doses of MMI (≥40 mg daily), and a delayed onset of presentation (2-4 weeks from exposure). The mechanism is unknown, although it is unlikely to be IgE-mediated given its time course. Current ATA guidelines recommend against using MMI or PTU in patients who have developed serious side effects to the other agent. Our case highlights the importance of close monitoring and timely follow-up after initiating anti-thyroid drugs.